2017
DOI: 10.1002/acm2.12101
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effective immobilization for whole brain radiation therapy

Abstract: To investigate the inter‐ and intra‐fraction motion associated with the use of a low‐cost tape immobilization technique as an alternative to thermoplastic immobilization masks for whole‐brain treatments. The results of this study may be of interest to clinical staff with severely limited resources (e.g., in low‐income countries) and also when treating patients who cannot tolerate standard immobilization masks. Setup reproducibility of eight healthy volunteers was assessed for two different immobilization techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Also, thermoplastic masks may not be suitable for claustrophobic patients, for which other immobilization strategies may be needed. 4 Finally, the current technique requires 36 hours to print the 3D-Head and 3D-NR for each patient. Therefore, this methodology would not be suitable for patients requiring WBRT within 1 to 2 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, thermoplastic masks may not be suitable for claustrophobic patients, for which other immobilization strategies may be needed. 4 Finally, the current technique requires 36 hours to print the 3D-Head and 3D-NR for each patient. Therefore, this methodology would not be suitable for patients requiring WBRT within 1 to 2 days.…”
Section: Discussionmentioning
confidence: 99%
“…Alternate techniques to immobilize patients for WBRT, such as ones based on the use of strip tapes instead of thermoplastic masks, had previously been evaluated for claustrophobic patients. 4 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al concluded that the comfort and tolerability was improved by using an open-face mask [3]. Even though an open-face mask causes less discomfort compared to a full-head mask, no mask at all would be even better [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The headrest was placed in the adapter, and the volunteer laid down. The volunteer's face was immobilized using two pieces of tape based on a low-cost immobilization technique published by Rubinstein et al14 This technique was chosen because it is a simple and robust immobilization technique that has been demonstrated to be able to provide sufficient immobilization for whole-brain radiotherapy, and it was easier to reproduce and verify compared to making a new thermoplastic mask for each of the volunteer trials. Once immobilized in the headrest, a reference scan of the volunteer was acquired in AlignRT Version 5.1 and a region of interest F I G .…”
mentioning
confidence: 99%